The Effectiveness of The NHT Learning Model in Improving The Learning Outcomes of Grade IV Students of Keleyan 2 Primary School in IPAS Subjects - Widiyati, Ayu; Yulianto, Muhammad; Abdillah, Mohammad; Marcos, Rafael (Journal of Action Research in Education, 2024)
This research was conducted with the aim of improving the learning outcomes of IPAS subjects for IV grade students at Keleyan 2 Primary School through the implementation of the NHT learning model. This research is a Classroom Action Research conducted in two cycles. Each cycle consists of planning, action implementation, observation, and reflection. The subjects in this classroom action research were fourth-grade students at Keleyan 2 Primary School, totaling 24 students. The data sources were from teachers and students. Data collection techniques used were interviews, questionnaires, written tests, and documentation. The data analysis technique used was qualitative and quantitative data analysis. The results of this research indicate that the implementation of the NHT learning model can improve the learning outcomes of IPAS subjects for fourth-grade students at SDN Keleyan 2, starting from the pre-cycle stage, cycle I, and cycle II. The learning outcomes in the pre-cycle percentage of 20.83%. Student learning outcomes improved in cycle I with a completion percentage of 83.3%. Then, in cycle II, a completion percentage of 95.8%. The conclusion of this research is that the implementation of the NHT learning model can improve the learning outcomes of IPAS subjects for fourth-grade students at SDN Keleyan 2.